The Consolidated Cash Statement of Federal Financial Transactions: Some Issues - Cohn, Samuel M. (The Review of Economics and Statistics, 1963)
say, the choice depends on one's notions about the determinants of various components of private expenditure, production lags, and the like.) (3) It would be useful if the policy section of the budget message were to point out what the NEB exercise shows to be the estimated effect of the budget on the public share, federal and state-local, in GNP, and on the nondefense public share, and if it were to make some comparisons with prior years. (Appropriate reference would have to be made to subsidies as reflecting some degree of federal absorption of output and also to federal finance of state and local purchases). (4) The policy section of the budget message should also point out the implications of the fiscal policy plan for the investment-consumption mix in the economy as a whole. (5) The lead table on budget by function should be supplemented by a larger table in which the expenditure figure for each function is broken down into purchases of goods and services, outright subsidies, transfer payments to individuals, grants-in-aid, interest, loans, and purchases of old (6) The above seven-way split should be carried through in the detailed discussion of the Federal Program by Function. (7) I would think it a bad idea -on grounds both of concept and of strategy -for the federal government to adopt a two-budget system involving a full-fledged capital account. Such a system would almost certainly result in the enthronement of the shibboleth that it is all right to debtfinance capital but the current budget should be balanced or in surplus. Except under very strong classical assumptions, such a rule would not assure neutrality as regards the saving-consumption choice, and would lose us an important degree of freedom, making it much more difficult to achieve through and monetary measures whatever total demand, income distribution, consumptioninvestment mix, and public-private balance we might desire. (A related secondary danger is that would come to be defined as bricks and mortar or the purchase of self-liquidating assets and, in particular, that investment in education, public health, etc., would not qualify.) (8) The above does not imply that we should continue to lump together public consumption and public investment. It would be most useful to distinguish, on the expenditure side of the budget, between consumption-type expenditures, investment in tangible assets, and what Musgrave calls expenditures for future benefit not resulting in acquisition of assets. The burden of (7) above is only that we should not associate particular receipts with particular types of expenditure.